Integration of on-chip perovskite nanocrystal laser and long-range surface plasmon polariton waveguide with etching-free process. Issue 28 (6th July 2022) - Lin, Hsin-Chang; Lee, Yang-Chun; Lin, Cheng-Chieh; Ho, Ya-Lun; Xing, Di; Chen, Mu-Hsin; Lin, Bo-Wei; Chen, Li-Yin; Chen, Chun-Wei; Delaunay, Jean-Jacques
Abstract : The coupling of on-chip perovskite nanocrystal lasers and the long-range surface plasmon polariton (LRSPP) waveguides is demonstrated with an etching-free lithographic patterning technique. Abstract : Perovskite materials prepared in the form of solution-processed nanocrystals and used in top-down fabrication techniques are very attractive to develop low-cost and high-quality integrated optoelectronic circuits. Particularly, integrated miniaturized coherent light sources that can be connected to light-guiding structures on a chip are highly desired. To control light propagating on a small footprint with low-loss optical modes, long-range surface plasmon polariton (LRSPP) waveguides are employed. Herein, we demonstrate an on-chip fabricated photonic-plasmonic hybrid system consisting of a perovskite lasing structure coupled to an LRSPP waveguide achieving a low lasing threshold and a propagation length over 100 μm. Preventing perovskite material degradation and the formation of surface roughness of the laser cavity during fabrication is made possible by designing a fabrication technique without any etching step.